Effect of catecholamines and β-blockers on linoleic acid desaturation activity - Tacconi de Gómez Dumm, Irma Nelva (1978)
The effect of catecholamines and adrenergic blocking agents on the oxidative desaturation of linoleic acid in rat liver microsomes was studied. Epinephrine (1 mg/kg/body weight) produced a significant decrease on the conversion of [1-14C]linoleic acid to gamma-linolenic acid. The effect of epinephrine was blocked by single injections of the beta blockers propranolol (10 mg/kg body weight) or dichloroisoproterenol 30 min before the hormone treatment. Isoproterenol (100 microgram/kg body weight) produced a significant decrease on the activity of the linoleyl-CoA desaturase. The effect of the catecholamines was postulated to be mediated through beta receptors by an enhancement of the intracellular levels of cyclic AMP.